Consideraciones climáticas sobre los convenios internacionales de relevancia ambiental - Foy Valencia, Pierre (2014)
In the first part we introduce what we consider the main features of the United Nations Framework Convention on Climate Change (CMCC) and its context, in terms of prejuridical issues about climate diplomacy and general considerations about this convention. In the second part, we discuss some references in order to show the synergies between the international agreements and the CMCC and some other more specific legal instruments.